Influence of the calcitonin assay on the definition of biochemical cure in patients with medullary thyroid carcinoma - Hartung-Knemeyer, V.; Müller, S.; Nagarajah, J.; Lahner, H.; Broecker-Preuss, M.; Bockisch, A.; Görges, R. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: Calcitonin (hCT) is an important diagnostic parameter in medullary thyroid carcinoma (MTC). We determined the variability of the reference ranges of several currently available immunometric assays for „biochemically cured“ MTC patients. Patients, methods: We compared six assays [Nichols ICMA, Biomerica IEMA, Immulite 2000 (Siemens), Calcitonin-IRMA magnum (Medipan), SELco-IRMA (Medipan) and Calcitonin IRMA (Medgenix)] in subgroups of 198 patients with differentiated thyroid cancer (DTC) after total thyroidectomy as a model for curatively treated MTC patients. In addition, hCT was measured after pentagastrin stimulation in 13 DTC patients and 13 patients with MTC. Results: The basal hCT concentrations were below the detection limit of the respective assay in 100% of all thyroidectomized DTC patients for Nichols ICMA (n = 138) and Immulite 2000 (n = 60), in 97% for Biomerica IEMA (n = 57), and in 85% for IRMA magnum (n = 20). However, basal hCT was mostly within the reference range in Selco-IRMA (n = 20) and Medgenix IRMA (n = 76). In all DTC patients and 9/13 MTC patients the pentagastrin stimulated hCT was below the detection limit for the Nichols ICMA and Immulite 2000, all four MTC patients with elevated stimulated hCT developed a recurrence during follow-up. Conclusions: For assays with high monomer specificity (Nichols ICMA, Biomerica IEMA, Immulite 2000, to a lesser degree IRMA magnum) biochemical cure is defined by basal and stimulated calcitonin levels below the detection limit. For assays with low monomer specificity (SELco-IRMA, IRMA Medgenix) calcitonin levels in the reference range of patients without thyroid diseases are consistent with “biochemical cure”.
Keywords: Calcitonin; tumour marker; medullary thyroid carcinoma; monomer-specific calcitonin assay; pentagastrin test; biochemical cure